ANALISIS KEBERLANJUTAN IKAN KERAPU SUNU (P. leopardus) DI KEPULAUAN SPERMONDE SULAWESI SELATAN - Ernaningsih Ernaningsih; Sitti Hadijah; Syahrul Djafar; Muhammad Yunus (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2023)
Grouper fish (P. leopardus) is one of the export commodities, where a very high fishing intensity causes overfishing. The management of catch fisheries that have been based on maximum sustainable results cannot accurately answer the problem of non-continuity comprehensively. FAO hints it needs to analyze ecological, economic, social, technological and legal-institutional factors. This research aims to determine the sustainability status of sunu grouper fish (P. leopardus) based on ecological, economic, social, fishing technology and law / institutional dimensions. These five dimensions identify sensitive attributes/factors and provide strategic and policy recommendations in support of sustainability. The study was conducted from June 2018 to September 2018, in the Spermonde Islands of South Sulawesi. The method used in this study is the survey method with the Rapfish technique. Based on Rapfish analysis and weight determination for sustainability showed that the value of the sunu grouper sustainability index in spermonde islands amounted to 32.97 (unsustainable).